PENGARUH PENGAWASAN GURU TERHADAP PRESTASI BELAJAR SISWA MADRASAH IBTIDAIYAH (MI) DARUL AKHLAQ DESA TORONAN PAMEKASAN - Kholik, Abd (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2021)
Education units require skilled and competent personnel to support efforts in carrying out various tasks so as to facilitate the achievement of educational goals. The principal of a madrasah as the leader of an educational institution should be able to maximize all the potential of teachers who have good learning competencies. The purpose of this study was examined because of two problems that became the main study in this study, first: about the presence or absence of the effect of teacher supervision on student achievement at Madrasah Ibtidaiyah (MI) Darul Akhlaq Toronan Pamekasan, second: how much influence teacher supervision has on student achievement in MadrasahIbtidaiyah (MI) Darul Akhlaq Toronan Pamekasan.Data collection methods are questionnaire instruments, interviews and documentation.Data collection lasted for one month, the data analysis technique used was statistical data analysis with product moment correlation technique. The results showed that there was an effect of teacher supervision on student achievement at Madrasah Ibtidaiyah (MI) Darul Akhlaq Toronan Pamekasan, with a moderate level of influence.This is proven by statistical data analysis which shows that the "r" work (0.487) is greater than the "r" of the moment product table at the 95% confidence level (0, 344) and if the "r" work is consulted with the correlation interpretation table, it is atrange 0.400 to 0.600.